Labor Market Transparency - Eskil Wadensjö (Institute for the Study of Labor (IZA), 2013)
The labor market differs from other markets in many respects. Most important is that those who supply labor also have to deliver it in person. It means firstly that the work environment and organization of work are important for those who deliver labor, since they are in the work place. Secondly, the result of a person's work varies with the price of labor (remuneration) and how the work is organized. Thirdly, the definition of work or a job for an employed person is not fixed but dependent on the person. The paper firstly deals with economic models of labor supply, labor demand, labor remuneration and labor market information. The subsequent sections discuss complications regarding labor market transparency in the context of international migration and public policy and policy implications regarding labor market transparency. A final section concludes.
Keywords: F22; J22; J23; J30; 330; transparency in the labor market; international migration; wages; labor supply; labor demand; labor market information